2014
DOI: 10.1016/j.jneumeth.2014.01.035
|View full text |Cite
|
Sign up to set email alerts
|

High resolution MRI anatomy of the cat brain at 3Tesla

Abstract: Background Feline models of neurologic diseases, such as lysosomal storage diseases, leukodystrophies, Parkinson’s disease, stroke and NeuroAIDS, accurately recreate many aspects of human disease allowing for comparative study of neuropathology and the testing of novel therapeutics. Here we describe in vivo visualization of fine structures within the feline brain that were previously only visible post mortem. New Method 3 Tesla MR images were acquired using T1-weighted (T1w) 3D magnetization-prepared rapid g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 53 publications
3
44
0
Order By: Relevance
“…They also identified some gyri and sulci, however it was not the main scope of their work. We think that most of these structures (gyri and sulci) are visible by high field MRI analysis, however this topic was not investigated in the present study, but can be found elsewere (Gray‐Edwards et al., ). The figures provided in our study allow for a better and more detailed anatomical differentiation within the feline cortex.…”
Section: Discussionmentioning
confidence: 73%
“…They also identified some gyri and sulci, however it was not the main scope of their work. We think that most of these structures (gyri and sulci) are visible by high field MRI analysis, however this topic was not investigated in the present study, but can be found elsewere (Gray‐Edwards et al., ). The figures provided in our study allow for a better and more detailed anatomical differentiation within the feline cortex.…”
Section: Discussionmentioning
confidence: 73%
“…MRI protocols are now available for dogs [59], cats [60], non-human primates [6163], pigs [64, 65] and sheep [66]. MRI (T1, T2, FLAIR) is advantageous for analysis of tissue volume and lesions [66], as well as for anatomical evaluation of particular brain areas [67].…”
Section: Introductionmentioning
confidence: 99%
“…In cases of hydrocephalus or ventriculomegaly, periventricular oedema is visualised in MRI. Thus, ventricular volume can be calculated incorrectly when marginal oedema surrounding cerebral ventricles is taken into consideration (Cherubini et al 2008;Gray-Edwards et al 2014). In our opinion, the difference in results may be the result of better visibility of the ventricular boundary in high-field MRI, while in low-field MRI the volume was miscalculated because marginal oedema was taken into consideration.…”
Section: Discussionmentioning
confidence: 86%
“…In other studies, the authors were able to observe and/or measure the lateral ventricles of healthy cats in low-and high-field MRI (Gray-Edwards et al 2014;Przyborowska et al 2017a;Przyborowska et al 2017b). In our study, ventricular volume was compared in different magnetic fields, and we were able to observe dilated ventricles in 17 cats and normal sized ventricles in three cats in both T1-weighted and T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%